2021
DOI: 10.3892/mmr.2021.12010
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA regulates microRNA‑125b/foxp3/caspase‑1 signaling and inhibits cell viability of nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is a common disease with high prevalence worldwide, affecting hundreds of thousands of patients every year. Although its progress can be inhibited by concurrent chemoradiotherapy and platinum-based agents, there is also a need for novel drugs to treat NPC. The present study identified tanshinone IIA as a potent drug that could suppress the proliferation of HK1 cells by enhancing pyroptosis via regulation of the miR-125b/foxp3/caspase-1 signaling pathway. Firstly, the effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In recent years, research has shown that TSA has a cytotoxic effect on a series of tumor cells, Liu et al found that TSA alleviated colorectal tumorigenesis through inhibition of intestinal inflammation 12 . Wang et al found that TSA inhibited cell viability of nasopharyngeal carcinoma through regulating microRNA‑125b/foxp3/caspase‑1 signaling 13 . However, the role of TSA against LUAD remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research has shown that TSA has a cytotoxic effect on a series of tumor cells, Liu et al found that TSA alleviated colorectal tumorigenesis through inhibition of intestinal inflammation 12 . Wang et al found that TSA inhibited cell viability of nasopharyngeal carcinoma through regulating microRNA‑125b/foxp3/caspase‑1 signaling 13 . However, the role of TSA against LUAD remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, miR-145/GSDMD signaling is regulated by tanshinone IIA, a lipophilic pharmacologically active compound extracted from Salvia miltiorrhiza Bunge (Danshen) ( 53 ). Similarly, tanshinone IIA enhances the pyroptosis in nasopharyngeal carcinoma (NPC) and suppresses the progression of NPC via miR−125b/foxp3/caspase−1/GSDMD signaling ( 54 ). Moreover, in enterovirus A71 (EV-A71)-infected human neuroblastoma, miR-195 inhibits pyroptosis by targeting NLRX1.…”
Section: Effects Of Ncrnas On Tumor Pyroptosismentioning
confidence: 99%
“…Specific miRNAs directly or indirectly participate in the regulation of multiple apoptotic pathways by regulating the level of downstream genes, and they can play an oncogenic or tumor suppressor role ( Bejarano et al, 2021 ). Tan IIA targets miR-125b/gasdermin D (GSDMD) and miR-145/caspase 1, which induces apoptosis of nasopharyngeal carcinoma (NPC) cells (HK1 cells) and cervical carcinoma cells (HeLa cells), respectively ( Tong et al, 2020 ; Wang et al, 2021c ). In addition, tan IIA targets miR30b, further upregulating p53 levels, which induces apoptosis and death of HCC cells ( Ren et al, 2017 ).…”
Section: Targeting Micrornas (Mirnas)mentioning
confidence: 99%